Malaysia's hotel energy management system (EMS) for energy efficiency improvement - Ahmad Rusdi, Fadli Hafiz (2014)
Energy management terms are rather defined by a different type of meaning by various types of people. For an industrial owner or sector, energy management is judicious or effectiveness usages of energy in order to maximize profit by minimizing the operation cost and enhance competitive positions. Performing energy management system for a hotel is rather critical to reduce operational cost. Since the consumption of energy in hotels depends on various factors, it was necessary to have a clear idea about some of the general characteristics that have proven to influence energy consumption in hotels; these include area, built up area, number of rooms and occupancy rates. This project study the potential of energy saving in one of the five star hotels located in Kuala Lumpur. The project aims to reduce the energy consumption of the building. Therefore, the methodology proposed are to analyze the potential of energy saving, life cycle cost and the payback period of the retrofit lighting system. Asoftware simulation called Relux Suite is used to simulate the existing lighting system and the alternative proposal for the outcome result in term of illumination factor and energy consumption. The output of the simulation then is compare between the existing and the several alternatives proposal. Then the commercial part for retrofitting the lighting system is briefly discussed in term of payback period and return of investment. The study found out that program proposed had potential of cost reduction by RM 1.8M per year with a minimum return of investment (ROl) of 4% - 8%. Based on the result, this case study has achieved its objective it term of commercial value but not for the building energy index which is estimated of 182.6 kWh/m2/year compared that is stated in MS 1525 standard which is 135 kWh/m2/year.